Newer propofol, ketamine, and etomidate derivatives and delivery systems relevant to anesthesia practice. Issue 2 (June 2018) - Hulsman, N.; Hollmann, M.W.; Preckel, B.
Abstract : Drug discovery is the cornerstone of developments in the field of anesthesia. Each year, new drugs enter the market and possibly change clinical practice. The development of new anesthetics can be divided into two groups. One strategy is the discovery of a new type of drug with unique molecular structure, better clinical properties, and lesser side effects than the already existing drugs. Another strategy is changing the molecular structure of current clinically available anesthetics to create new drugs with better pharmacokinetic and pharmacodynamic properties. In this review, we describe the current developments of frequently used anesthetics, namely, propofol, etomidate, and ketamine. Alfaxalone is an old anesthetic with favorable properties such as hemodynamic and respiratory stability but lacks appropriate vehicle. New formulations with recently developed solvents together with this old anesthetic are created. Next to drug development, there is also a constant search for better delivery systems for the already available anesthetics. Following open-loop systems like TIVA, new closed-loop systems have entered the market. We also discuss about SEDASYS®-Computer-Assisted Personalized Sedation System, an automatic closed-loop delivery system that provides propofol sedation for endoscopic procedures.